Mengungkap Struktur Permukiman Komunitas Akur (Adat Karuhun Urang) Cigugur Kabupaten Kuningan - Indratno, Imam; Agustina, Ina H; Chamid, Chusarini; Siddik, Ansharsyah M; Kuntoro, Sena H (Universitas Diponegoro, Indonesia, 2020)
The Karuhan Urang Indigenous Community (AKUR) Cigugur, West Java, is one of the traditional communities that still adheres to the Sunda Wiwitan belief. This community lives side by side with mutual respect for the views of other religions. At the Seren taun ceremony, people from various religions attended and prayed together in Paseban Tri Panca Tunggal. The preservation of Paseban Tri Panca Tunggal is an effort to continue the tradition of the community's ancestors, Prince Sadewa Madrais Alibasa. Ancestral teachings embedded in society are manifested in the form of strong tolerance and a sense of universal brotherhood in the Cigugur Indigenous Community. The study uses a structuralism approach to uncover the structure of settlements consisting of aspects of the form and function of the settlement elements. With syntagmatic analysis, research seeks to look for relations between elements of settlements and reveal the meaning of elements of the settlement system. Cultural identity of the people who uphold the values of humanity and nationality can be a cultural capital for the Cigugur Village development process.